Does pain relief with spinal cord stimulation for angina conceal myocardial infarction?. Issue 5 (May 1994) - Andersen, C.; Hole, P.; Oxhøj, H.
Abstract : OBJECTIVE--To investigate the possibility that spinal cord stimulation (SCS) used for pain relief can conceal acute myocardial infarction (AMI). DESIGN--Prospective evaluation of patients treated with SCS. SETTING--University hospital. PATIENTS--50 patients with coronary artery disease and severe, otherwise intractable angina treated with SCS for 1-57 months. MAIN OUTCOME MEASURES--Necropsy findings, symptoms, serum enzyme concentrations, electrocardiographic changes. RESULTS--Ten patients were considered to have had AMI. In nine of these SCS did not conceal precordial pain and in one patient no information about precordial pain could be obtained. CONCLUSION--There was no evidence that SCS concealed acute myocardial infarction.